1997
DOI: 10.3171/jns.1997.86.5.0859
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraluminal or extraluminal endothelin on perfused rabbit basilar arteries

Abstract: The authors investigated selective intra- and extraluminal effects of endothelin (ET) on perfused basilar and extracranial arteries and also studied the interaction between ET and extraluminal oxyhemoglobin (oxyHb). The basilar, mesenteric, and femoral arteries were isolated from 23 Japanese White rabbits. After isolation of the intra- and extraluminal sides of the preparation, 3 x 10(-10) to 3 x 10(-8) mol/L of ET was administered intra- or extraluminally. After extraluminal pretreatment with 10(-5) mol/L oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…However, ET-1 concentrations in CSF and plasma are in the picomolar range, levels unlikely to be capable of causing significant contraction. 27 Most of the ET would be released locally and, therefore, would not reach the systemic circulation, thus yielding local concentrations of immunoreactive ET much higher at the vascular endothelium-smooth muscle interface than in the blood stream. 2,32,46,49,62 Endothelin should be regarded more as a paracrine than as an endocrine hormone.…”
Section: Endothelin-1 Synthesis and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ET-1 concentrations in CSF and plasma are in the picomolar range, levels unlikely to be capable of causing significant contraction. 27 Most of the ET would be released locally and, therefore, would not reach the systemic circulation, thus yielding local concentrations of immunoreactive ET much higher at the vascular endothelium-smooth muscle interface than in the blood stream. 2,32,46,49,62 Endothelin should be regarded more as a paracrine than as an endocrine hormone.…”
Section: Endothelin-1 Synthesis and Functionmentioning
confidence: 99%
“…32,35,52,59,65 Both intra-and extraluminal ET have displayed potent and dose-dependent vasoconstricting effects on basilar arteries. 27 The effects of intraluminal (but not extraluminal) ET was enhanced by extraluminal oxyHb and N G -monomethyl-L-arginine, an inhibitor of endothelial NO syn- Tables 1 and 2 for classifications of phases and hypodense area groups. Vasospasm was estimated on the basis of postoperative angiograms obtained within 5 to 14 days post-SAH.…”
Section: Endothelin-1 Synthesis and Functionmentioning
confidence: 99%
“…In the clinical setting of aneurysmal SAH, synthesis of ETs may be stimulated by several substances present in the subarachnoid blood clot, such as oxyhemoglobin, 27,28,37 thrombin, 30 and transforming growth factor ␤-1. 33 In the "endothelin hypothesis" it is suggested that an abluminal clot stimulates vascular endothelium to produce ETs and that ET-1 and its intermediate precursor, big ET-1, are among the factors inducing the prolonged vasoconstriction of vasospasm.…”
Section: Discussionmentioning
confidence: 99%
“…33 In the "endothelin hypothesis" it is suggested that an abluminal clot stimulates vascular endothelium to produce ETs and that ET-1 and its intermediate precursor, big ET-1, are among the factors inducing the prolonged vasoconstriction of vasospasm. 27,28,31,37,48,50 Studies in which elevated post-SAH serum and CSF ET concentrations are reported are usually performed in patients undergoing neurosurgical operations, such as craniotomy and clipping of the ruptured aneurysm. 12,36,42,44 The influence of such major surgical interventions on ET levels is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…They found a statistically significantly greater effect (p < 0.01) of ET on the basilar arteries than on the femoral or mesenteric arteries. 31 However, this problem remains to be elucidated in further investigations.…”
Section: Hypotensionmentioning
confidence: 97%